Iranian efl and indian esl college students’ beliefs about reading strategies in l2 (2010)
The notion of “learner beliefs” has garnered much attention in the field of second language acquisition. Although different studies have been conducted to study learners’ beliefs about language learning, little research has looked into the issue of L2 readers’ beliefs and their relations to reading strategies. This study investigated whether there are any significant differences between efl and ESL readers in reading awareness of metacognitive strategies use when they are reading in English. 190 undergraduate college students completed the Survey of Reading Strategies questionnaire. The results indicated that the subjects in both groups reported almost similar patterns of strategy awareness while reading; however, Indians reported more awareness of global, support and total metacognitive reading strategies than Iranians while no significant difference was reported when using problem-solving strategies. These results can contribute to the necessity of reading strategies training in both contexts. La noción de “creencias del estudiante” ha ganado mucha atención en el ámbito de la adquisición de la segunda lengua. Aunque se han realizado diferentes estudios sobre las creencias de los estudiantes respecto al aprendizaje de la lengua, poco se ha investigado acerca de las creencias de los lectores de segunda lengua y su relación con estrategias de lectura. Este estudio investigó si había diferencias significativas entre los lectores de inglés como lengua extranjera y los lectores de inglés como segunda lengua en cuanto a la conciencia lectora y el uso de estrategias metacognitivas cuando leen en inglés. Ciento noventa estudiantes de pregrado completaron el cuestionario sobre estrategias lectoras. Los resultados mostraron que los sujetos de los dos grupos reportaron un patrón casi similar al uso de conciencia de estrategia mientras leían. Sin embargo, los estudiantes indios reportaron ser más conscientes respecto a estrategias metacognitivas lectoras totales, globales y de apoyo que los estudiantes iraníes, mientras que no se hallaron diferencias significativas al usar estrategias para la resolución de problemas. Estos resultados pueden contribuir a la necesidad de capacitación en estrategias lectoras en ambos contextos.